Reconnaissance of Canal de Haro & Strait of Rosario and approaches &c &c - http://id.worldcat.org/fast/609868 (1858)
1 item extracted from FO 115/205 (folio 231). 'Reconnaissance of Canal de Haro & Strait of Rosario and approaches &c &c': tracing of United States Coast Survey chart, coloured to show four suggested boundary lines between British Columbia and the United States of America. Key to boundaries. Copied by G H Richards, Capt HMS Plumper, January 1858. [Haro and Rosario Straits, 1854; 1858]